A new lanthanum coordination polymer built from a semi‐rigid tripodal carboxylic acid ligand: synthesis, crystal structure and properties. Issue 9 (19th August 2019) - Zhou, Lian; Shi, Pei-Dong; Guo, Xiao-Kun; Feng, Xiu-Cun; Wang, Lin-Lin; Zhang, Jun
Abstract : A new lanthanum coordination polymer was prepared by employing a semi‐rigid multidentate carboxylic acid ligand. It possesses (3, 6)‐connected two‐dimensional kgd topology sheets consistsing of secondary building units of La2 clusters and 4, 4′, 4′′‐{[(2, 4, 6‐trimethylbenzene‐1, 3, 5‐triyl)tris(methylene)]tris(oxy)}tribenzoate ligands, which further stack into three‐dimensional supramolecular networks through π–π interactions. Abstract : By employing the semi‐rigid multidentate carboxylic acid ligand 4, 4′, 4′′‐{[(2, 4, 6‐trimethylbenzene‐1, 3, 5‐triyl)tris(methylene)]tris(oxy)}tribenzoic acid (denoted H3 L ), a new lanthanum coordination polymer, namely poly[[bis(dimethylformamide)(μ6 ‐4, 4′, 4′′‐{[(2, 4, 6‐trimethylbenzene‐1, 3, 5‐triyl)tris(methylene)]tris(oxy)}tribenzoato)lanthanum(III)] dimethylformamide tetrasolvate 0.25‐hydrate], {[La(C33 H27 O9 )(C3 H7 NO)2 ]·4C3 H7 NO·0.25H2 O} n or {[La( L )(DMF)2 ]·4(DMF)·0.25(H2 O)} n (DMF is dimethylformamide) (1 ), was prepared and characterized by single‐crystal X‐ray diffraction, elemental analysis, thermogravimetric analysis, IR spectroscopy and photoluminescence studies. The asymmetric unit contains one La III cation, one anionic L 3− ligand, two coordinated DMF molecules, four free DMF molecules and one‐quarter of a free water molecule. Compound1 possesses (3, 6)‐connected two‐dimensional kgd topology sheets consisting of secondary building units of La2 clusters and L 3− ligands, which further stack into three‐dimensional supramolecular networks through π–π interactions. Compound1 exhibits a photoluminescence emission at room temperature, with a peak at 410 nm, owing to a ligand‐centred excited state.